Caregivers Systematically Overestimate Their Child's Height-for-Age Relative to Other Children in Rural Ethiopia. Issue 5 (31st January 2022) - Passarelli, Simone; Sudfeld, Christopher; Davison, Kirsten K; Fawzi, Wafaie; Donato, Katherine; Tessema, Masresha; Gunaratna, Nilupa S; De Groote, Hugo; Cohen, Jessica; McConnell, Margaret
ABSTRACT: Background: Stunting affects one-quarter of children <5 y of age, yet little is known about the accuracy of caregivers' perceptions regarding their child's linear growth. Most existing quantitative research on this topic has been conducted in high-income countries and has examined perceptions of children's weight rather than height. Objectives: In rural Ethiopia where linear growth faltering is highly prevalent, this study aimed to better understand how caregivers perceive their child's growth. The objectives of this analysis were to 1 ) assess caregivers' perceptions of their child's height; 2 ) investigate whether there is a discrepancy between a child's actual height and caregivers' perceptions of their child's height; and 3 ) examine the factors that influence discrepancies in estimating a child's height (secondary outcomes), including the role of the average height in the community (primary outcome). Methods: We conducted a cross-sectional analysis using data from 808 woman caregivers of children ages 6–35 mo in the Oromia region of Ethiopia. We assessed caregivers' rankings (from 1 to 10) of their child's height relative to other children their age in their village. We then converted these rankings to z scores based on an age- and region-specific distribution in order to calculate their difference with the child's actual height-for-age z score and to determine the degree of overestimation. Lastly, we used multivariate log Poisson regressions to determine factors associated with overestimating a child's height. Results: Forty-three percent of caregivers scored their child's height as the median; 37% overestimated their child's height relative to other children. Regression results showed caregivers who were poorer, and had children who were female, older, and stunted, were more likely to overestimate. Conclusions: Our findings suggest that caregivers of young children in Oromia systematically overestimated their children's height, which could adversely affect child health if these misperceptions translate to insufficient care-seeking behavior or feeding choices for children.